The effect of beam arrangements and the impact of non‐coplanar beams on the treatment planning of stereotactic ablative radiation therapy for early stage lung cancer. Issue 1 (14th July 2015) - Fitzgerald, Rhys; Owen, Rebecca; Barry, Tamara; Hargrave, Cathy; Pryor, David; Bernard, Anne; Lehman, Margot; Mai, Tao; Fielding, Andrew
Abstract: Introduction: The aim of this study was to compare various coplanar and non‐coplanar 3‐dimensional conformal radiation therapy (3DCRT) beam arrangements for the delivery of stereotactic ablative radiation therapy (SABR) to patients with early stage lung cancer, based on the dosimetric criteria from the Radiation Therapy Oncology Group (RTOG) 1021 protocol. Methods: Ten medically inoperable lung cancer patients eligible for SABR were re‐planned using three different coplanar and three different non‐coplanar beam arrangements. The plans were compared by assessing planning target volume (PTV) coverage, doses to normal tissues, the high‐dose conformity (conformity index) and intermediate dose spillage as defined by the D2cm, (the dose at any point 2 cm away from the PTV), and the R50% (the ratio of the volume of half the prescription dose to the volume of the PTV). Results: Sixty plans in total were assessed. Mean PTV coverage with the prescription isodose was similar between coplanar (95.14%) and non‐coplanar (95.26%) techniques ( P = 0.47). There was significant difference between all coplanar and all non‐coplanar fields for the R50% ( P < 0.0001) but none for the D2cm ( P = 0.19). The seven and nine field beam arrangements with two non‐coplanar fields had less unacceptable protocol deviations (10 and 7) than the seven and nine field plans with only coplanar fields (13 and 8). The 13 field coplanar fields did not improve protocol compliance with eight unacceptable deviations. The 10 field non‐coplanar beam arrangement achieved best compliance with the RTOG 1021 dose criteria with only one unacceptable deviation (maximum rib dose). Conclusion: A 3DCRT planning technique using 10 fields with ≥6 non‐coplanar beams best satisfied high and intermediate dose constraints stipulated in the RTOG 1021 trial. Further investigations are required to determine if minor protocol deviations should be balanced against efficiency with the extended treatment times required to deliver non‐coplanar fields and if treatment times can be improved using novel intensity modulated techniques. Abstract : Comparison of six different beam arrangements for lung stereotactic ablative radiation therapy.